Corporate governance and accountability - SOLOMON, Jill (John Wiley & Sons, 2004)
Corporate governance is concerned with how a company is directed and controlled and, in particular, with the role of the directorate and the need to ensure that there is an effective framework for accountability of directors to owners. Corporate Governance and Accountability, Third Edition provides readers with an up–to–date summary of the most recent developments in corporate governance. The book provides a full discussion of corporate governance issues and adopts a holistic approach to corporate governance. It provides a full discussion of corporate governance issues, taking the broadest view of the corporate governance agenda, including both theory and practice. The new edition is comprehensively updated and incorporates new codes of practice, policy documents and academic research.